Evidentials in the Iberian Peninsula and the Romance languages: from ergativity to language contact - Lara Bermejo, Víctor (2022)
The focus in the spread of morphological evidentiality in Peninsular Spanish can be located in western Spain. From that area, the resource of morphological evidentiality has gradually diffused throughout all of Peninsular Spanish, as well as European Portuguese, Galician and much of Catalan. The generalisation of evidentiality elsewhere has followed the same path: there is always an epicentre from which this strategy expands. This paper analyses the linguistic reasons that justify the birth of evidentiality in western Spain, and the importance that language contact has had in the extension of evidentials throughout the Iberian Peninsula and the whole Romance spectrum. The results show that evidentiality is either the result of ergative patterns or a feature adopted by contact.